Stress Management of Pregnant Women in Preventing Preeclampsia: Qualitative Interview Study - Hasnah; Rasmawati; Fadhilah Gani, Nurul; Rasdiyanah; Nurhidayah; Adhiwijaya, Ardian; Ilhamsyah; Subu, Muhammad Arsyad (Jurnal Kesehatan Manarang, 2025)
Maternal mortality remains a critical issue in Indonesia, predominantly caused by the triad of haemorrhage, preeclampsia, and infection. The progression from haemorrhage to preeclampsia and ultimately infection presents a serious threat to maternal health. From a nursing perspective, early prevention strategies, including stress management, are essential in reducing the risk of preeclampsia among pregnant women. This study aims to explore the lived experiences of pregnant women in managing stress as a non-pharmacological nursing intervention to prevent preeclampsia. A qualitative descriptive design has been employed to explore stress management strategies among pregnant women in the context of preeclampsia prevention. Participants were selected through purposive sampling and recruited from two primary healthcare centres. Data were collected over two months using in-depth interviews and focus group discussions (FGDs). All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using OpenCode software for systematic coding and interpretation. The thematic analysis has identified three overarching themes: (1) Sources and experiences of stress during pregnancy; (2) Emotional shifts associated with pregnancy; and (3) Coping strategies adopted to prevent preeclampsia. The third theme included three sub-themes: the use of relaxation techniques to manage stress, the application of distraction methods to redirect stress, and the integration of spiritual practices as a means of emotional regulation. Pregnant women utilize a variety of distraction, relaxation, and spiritual strategies to alleviate stress and manage emotional fluctuations during pregnancy, thereby helping to prevent an increase in blood pressure. This study suggests that preeclampsia prevention can be achieved effectively and economically through non-pharmacological nursing interventions. Future research should consider a larger and more diverse population, potentially incorporating a transcultural nursing approach, to further explore these interventions' applicability across different cultural contexts.